Diagnostic and prognostic classification of atypical spitzoid tumours based on histology and genomic aberrations: A prospective cohort study with long-term follow-up. (March 2022) - Gassenmaier, Maximilian; Soltanpour, Narges; Held, Laura; Metzler, Gisela; Yazdi, Amir S.; Brecht, Ines B.; Schneider, Dominik T.; Stadler, Rudolf; Garbe, Claus; Bauer, Jürgen
Abstract: Background: Histological classification of atypical spitzoid tumours (ASTs) is unreliable, and categorisation of these lesions into benign and malignant is poorly reproducible. Here, we classified ASTs based on histology and chromosomal aberrations and explored the prognostic significance of genomic aberrations in a prospective cohort with a long-term follow-up. Patients and methods: Histologically equivocal ASTs from 76 patients were analysed by array comparative genomic hybridisation (aCGH). Tumours were histologically assessed by a panel of dermatopathologist before and after aCGH and classified as benign, ambiguous or malignant. Chromosomal aberrations were correlated with an outcome. Results: Chromosomal aberrations were detected in 45 (59%) of 76 ASTs (median age: 16 years, range: 0–74; median follow-up: 90 months, range: 13–153). The initial histological diagnosis was changed upon presentation of aCGH results in 36 of 76 cases (47%). The final diagnostic interpretation classified 61% of the lesions as benign, 18% as ambiguous and 21% as malignant. Positive sentinel lymph node biopsies (6+/29) occurred at similar rates in all diagnostic groups ( P  = 0.83) and were not associated with an unfavourable outcome. Two patients had local recurrences, but none of the patients developed metastasis beyond the sentinel lymph node. Conclusions: All ASTs had an excellent prognosis, even in cases with worrisome morphology and chromosomal aberrations. With no distant metastasis or death in long-term follow-up of 76 patients, no correlation between chromosomal aberrations and prognosis was possible. However, it seems likely that in larger cohorts, metastases would arise in cases with complex aberrations and these patients should undergo clinical follow-up. Highlights: Atypical spitzoid tumours (ASTs) exhibit a continuum of chromosomal aberrations. Histology of ASTs does not reliably reflect the extent of chromosomal aberrations. ASTs with and without chromosomal aberrations have an excellent prognosis. Sentinel lymph node status has no prognostic relevance in ASTs. ASTs with complex chromosomal aberrations should undergo clinical follow-up.